Interferons in Sjögren’s Syndrome: Genes, Mechanisms, and Effects - Li, He; Ice, John A.; Lessard, Christopher J.; Sivils, Kathy L. (Frontiers in Immunology, 2013)
Sjögren’s syndrome (SS) is a common, progressive autoimmune exocrinopathy distinguished by dry eyes and mouth and affects ~0.7% of European population. Overexpression of transcripts induced by interferons (IFN), termed as an ‘IFN signature’, has been found in SS patients. Four microarray studies have been published in SS that identified dysregulated genes within type I IFN signaling in either salivary glands or peripheral blood of SS patients. The mechanism of this type I IFN activation is still obscure, but several possible explanations have been proposed, including virus infection-initiated and immune-complex-initiated type I IFN production by plasmacytoid dendritic cells (pDCs). Genetic predisposition to increased type I IFN signaling is supported by candidate gene studies showing evidence for association of variants within IFN-related genes. Once activated, IFN signaling may contribute to numerous aspects of SS pathophysiology, including lymphocyte infiltration into exocrine glands, autoantibody production, and glandular cell apoptosis. Thus, dysregulation of IFN pathways is an important feature that can be potentially used as a serum biomarker for diagnosis and targeting of new treatments in this complex autoimmune disease.